Mutational Analysis of Eggplant Latent Viroid RNA Circularization by the Eggplant tRNA Ligase in Escherichia coli - Cordero, Teresa; Ortolá, Beltrán; Daròs, José-Antonio (Frontiers in Microbiology, 2018)
Eggplant latent viroid (ELVd) is a relatively small non-coding circular RNA that induces asymptomatic infections in eggplants (Solanum melongena L.). Like other viroid species that belong to the family Avsunviroidae, ELVd contains hammerhead ribozymes in the strands of both polarities that self-cleave RNAs producing terminal 5’-hydroxyl and 2’,3’-cyclic phosphodiester groups. Available experimental data indicate that ELVd replicates in the chloroplasts of infected cells through a symmetric rolling-circle mechanism, in which RNA circularization is catalyzed by the chloroplastic isoform of the tRNA ligase. In this work, a mutational analysis was performed to gain insight into the sequence and structural requirements of the tRNA ligase-mediated circularization of ELVd RNAs. In the predicted minimum free energy conformation of the monomeric linear ELVd RNA intermediate of plus (+) polarity, the ligation site is located in the lower part of an opened internal loop, which is present in a quasi-rod-like structure that occupies the center of the molecule. The mutations analyzed herein consisted of punctual nucleotide substitutions and deletions surrounding the ligation site on the upper and lower strands of the ELVd quasi-double-stranded structure. Computational predictions of the mutated ELVd conformations indicated different degrees of distortions compared to the minimum free energy conformation of the wild-type ELVd linear monomer of + polarity. When these mutant RNAs were expressed in E. coli, they were all circularized by the eggplant tRNA ligase with approximately the same efficiency as the wild-type ELVd, except for those that directly affected the ribozyme domain. These results suggest that the viroid ribozyme domains, in addition to self-cleavage, are also involved in the tRNA ligase-mediated circularization of the monomeric linear replication intermediates.